Exploring English Language Learning through Online Gaming: A Case Study of Two Children - Mafulah, Siti; Mhirda, Maftuch Junaidy; Haider, Sanwal (JEES (Journal of English Educators Society), 2025)
Online games are often considered as a disturbance for children, negatively affecting time management, encouraging undesirable habits, and contributing to poor academic performance. While several studies have examined the effects of online games on students, in-depth exploration at the individual level remains limited. Therefore, this study investigates the potential of online games in influencing children's English language acquisition. A case study was employed, with data collected through semi -structured interviews with children and parents. Observations of children while playing online games were conducted, along with an analysis of documents such as school assignments. The findings show that the child who played online games more frequently demonstrated a stronger grasp of English vocabulary, greater fluency in speaking, and a better ability to respond to questions about words meanings compared to child who played less frequently. Both children, however, met the minimum standard score of the English subject at school. Furthermore, several benefits of learning English through online games were identified, including increased motivation and confidence. The study also suggests that examining factors such as language aptitude, learning strategies, and environ mental support in the context of online gaming may provide a more comprehensive understanding of how online games can be utilized to enhance children's English language learning.HIGHLIGHTS: Learning English through online games based: in this research, learning English through online games need a supportive environment provided by parents, teachers, and peers. It is a vital role in fostering motivation and building children’s confidence in using English. It is essential for parents to recognize that each child possesses unique learning styles and abilities Increase English ability through game-based: through online game, children increase their English abilities. Child A and B is also reflected in their English subject scores at school. Child A consistently earns higher scores than Child B, which indicates a better understanding of English grammar and sentence structure. Learning English through online games raise children’s motivation. It is confirmed that after approximately six months of playing online games, Child A and B become more motivated to learn English at school. They were eager to complete homework assignments and shared their experience at school, and motivated to speak in English.